Kemampuan representasi matematis siswa dalam menyelesaikan soal barisan dan deret berorientasi hots ditinjau dari self-efficacy - Parhusip, Christhoper; Rahmatina, Desi; Izzati, Nur (Jurnal Pendidik Indonesia, 2025)
Mathematical representation ability is a crucial aspect of mathematics learning as it reflects how students understand, process, and communicate mathematical concepts in various forms. This study aims to describe students’ mathematical representation ability in terms of their levels of self-efficacy. A descriptive qualitative approach was employed, involving six eleventh-grade students who were categorized into high, moderate, and low self-efficacy groups. The instruments used included a mathematical representation ability test and an interview guide. The findings indicate that students with high self-efficacy were able to fulfill all indicators of mathematical representation—verbal, symbolic, and visual. Students with moderate self-efficacy demonstrated mastery of the verbal and symbolic indicators but were not yet able to meet the visual indicator. Meanwhile, students with low self-efficacy were unable to meet the three indicators of representation optimally. These findings suggest that students’ self-efficacy levels influence the quality of their mathematical representation ability. The higher the self-efficacy, the greater the students’ tendency to think systematically, confidently, and flexibly in representing mathematical ideas.